Appropriateness in Dentistry: A Survey Discovers Improper Procedures in Oral Medicine and Surgery - Giacomo Oteri; Vera Panzarella; Antonia Marcianò; Olga Di Fede; Laura Maniscalco; Matteo Peditto; Giuseppina Campisi (International Journal of Dentistry)
Objectives. The aim of this study was to assess appropriateness of diagnostic exams, treatments, and procedures among Italian dental practitioners. Materials and Methods. A questionnaire with multiple responses on topics of dentistry and oral medicine was administered to a sample of 198 Italian dental practitioners. Information on characteristics of the respondents was also collected. Descriptive statistics and multiple correspondence analysis (MCA) were applied. Data were analyzed using R software (version 3.3.2). Results. The survey respondents included Doctors of Medicine (MD) (54/198 = 27%) with or without specialty in dentistry (33% versus 67%), Doctors of Dental Surgery (DDS) (144/198 = 73%), DDS with specialty in orthodontics (7%), and DDS with specialty in oral surgery (4%). Mandatory procedures in dental and oral medicine education and training include (a) prescription of antibiotics before/after oral surgery procedures; (b) prevention strategies for oral cancer, and (c) prescription of dental X-ray examinations (41%, 52%, and 48%, resp.). Conclusion. On examining the results of the survey, it is evident that information and implementation of the above mentioned procedures are crucially needed. Our results confirm the necessity to reduce inappropriate practices in dentistry, implementing formation and information, leading to correct prescriptions, and optimizing patients’ oral health. This coincides with the Italian Slow Medicine program entitled “Fare di più non significa fare meglio–Choosing Wisely Italy,” which has also motivated this study.